2001
DOI: 10.1046/j.1526-4610.2001.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Statuslike SUNCT in Two Young Women

Abstract: Objective.-To describe the statuslike pattern of SUNCT (short-lasting unilateral neuralgiform pain with conjunctival injection and tearing) in two young women.Background.-SUNCT syndrome is a rare condition characterized by a short-lasting periocular pain associated with marked autonomic symptoms. Twenty-five cases have been reported in the literature with a high preponderance of males and a mean age of 51 years. The frequency of episodes shows a wide variability, not just among individuals but also in the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 10 publications
0
37
0
Order By: Relevance
“…Attacks may be as infrequent as once daily or less to more than 60 per hour [12]. Objective assessment of the frequency of attacks in four patients demonstrated a mean of 16 attacks daily, with a range of 1 to 86 attacks daily [13].…”
Section: Frequency and Periodicity Of Attacksmentioning
confidence: 94%
See 1 more Smart Citation
“…Attacks may be as infrequent as once daily or less to more than 60 per hour [12]. Objective assessment of the frequency of attacks in four patients demonstrated a mean of 16 attacks daily, with a range of 1 to 86 attacks daily [13].…”
Section: Frequency and Periodicity Of Attacksmentioning
confidence: 94%
“…The individual short-lasting attacks are brief, lasting between 2 and 600 seconds [7,11,12]. In addition, the authors observed a SUNCT patient for whom all of the attacks lasted between 8 and 20 minutes, thus extending the range of duration of short-lasting SUNCT attacks (Matharu et al, unpublished observations).…”
Section: Duration Of the Individual Attackmentioning
confidence: 95%
“…The area corresponding to the first branch of the trigeminal nerve is the most commonly reported, but other parts have been described as well [2,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…SUNCT or SUNA may occasionally present with statuslike exacerbations, with up to 60 attacks in an hour [4]. Occasionally, these patients will require hospitalization to control symptoms, which may prevent them from drinking or chewing.…”
Section: Intravenous Lidocaine In the Treatment Of Sunct And Sunamentioning
confidence: 99%
“…Cluster headache (CH), shortlasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT), and short-lasting unilateral neuralgiform headache attacks with cranial autonomic symptoms (SUNA) are TACs that occasionally require emergency treatment. SUNCT and SUNA are especially refractory to treatment with acute analgesics, including opioids [2,3], and may present with status-like frequency, requiring urgent treatment [4,5]. Lidocaine and mexiletine are antiarrhythmic medications that appear safe and effective in the treatment of various pain disorders, including neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%